Determinan yang Memengaruhi Pemilihan Saluran Pemasaran Bunga Potong Krisan di Kabupaten Cianjur - Wisnu Ardi Pratama; Rita Nurmalina; Nia Rosiana (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2023)
Chrysanthemum is one of the main commodities in Cianjur Regency with 52% of the total chrysanthemum production in West Java Province. This study aims to analyze the determinants that influence the choice of marketing channels for chrysanthemum farmers in Cianjur Regency. Farmers have two choices of marketing channels to distribute their chrysanthemum cut flowers to final consumers, namely through collectors and also through wholesalers in Rawabelong Market. The most efficient marketing channel is channel 2, where farmers sell to wholesalers in the swamp belong before finally selling to the final consumers. The channel most chosen by farmers is channel 1, in which farmers sell their chrysanthemum cut flowers to the collectors and then from the collectors they sell them to wholesalers in Rawabelong Market, before being received by the final consumers. Respondents in this study were chrysanthemum cut flower farmers in two central districts, namely Cugenang District and Sukaresmi District, with a total of 60 farmers. This research was analyzed using binary logistic regression analysis by setting efficient marketing channels as the reference variable. The results of this study indicate that there are 6 factors that influence the choice of marketing channels, namely age (-), education (+), sales volume (+), price per bundle (+), capital bond (-) and transportation costs (+). Farmers prefer to sell to collectors (channel 1) because of the attachment of capital to collectors due to the lack of capital owned by farmers. Another factor is that as they get older, farmers tend to choose inefficient channels. In addition, the increasing length of education, sales volume, bond price, and transportation costs incurred, farmers tend to choose the efficient channel (channel 2). This research has policy implications for the regional government, especially the Cianjur Regency Agriculture Service, so that they can provide capital assistance in the form of seeds, fertilizers and financial so that farmers do not depend on village collectors for capital.